Dropout of Vaccination Among Iraqi Children - Kadim, Maha. A.; Abdulhasan, Anees Flayyih; Abdulrasol, Zainab Abdulameer; Obaid, Ali Fadhil (South Asian Journal of Social Sciences and Humanities, 2022)
Immunization has been a successful method of preventing and controlling life-threatening  infectious diseases since the 20th century. About 2-3 million child deaths are avoided annually  through vaccination. Despite increasing vaccination rates worldwide, many children in  developing nations still miss their vaccinations. Therefore, many children are still vulnerable  to the Expanded Program on Immunization (EPI) targeted diseases. Missed opportunities for  vaccination (MOVs) occur when people who are eligible for vaccination visit a medical facility  but do not receive the necessary vaccinations. Therefore, vaccination has the opportunity to  achieve more if missed vaccination opportunities (MOVs) are removed and global  immunization coverage increases. A narrative review was conducted to summarize vaccination  missing among Iraqi children, and factors affecting the vaccine coverage rate.
Keywords: vaccination; dropout; Iraqi; children